Morphology of the lectotype of Chelodina oblonga Gray 1841 (Testudines: Chelidae) - Smales, Ian (Zootaxa, 2021)
Uncertainty about taxonomy and nomenclature of the Australian long-necked turtle Chelodina oblonga has ensued since its description by Gray in 1841. This has been due to the general nature of information about provenance of the lectotype specimen and the ostensible morphological similarity of the specimen to another taxon from northern Australia that confused Gray and many subsequent workers. The south-western Australian provenance of the specimen has recently been confirmed by Shea et al. (2020). The present paper provides a detailed consideration of morphology of the specimen and compares it with other specimens available to Gray and to larger series that are now available. The study elucidates morphological aspects that have underlain the history of confusion and it highlights a number of characters that consistently differentiate adults of the relevant taxa. These demonstrate that morphology of the C. oblonga lectotype conforms with the taxon from the south-west of Western Australia, as has also been confirmed by recently published investigations of mitogenomics and historical information about provenance of the lectotype.